Faktor Penentu Tingkat Efisiensi Kinerja Perbankan - Sofiana Istinfarani; Fika Azmi (ITB AAS INDONESIA, 2020)
This study aims to examine the determinants of the level of efficiency of banking performance as measured by the non-parametric Data Envelopment Analysis (DEA) method. The determinants of the level of efficiency in banking performance include bank size, Capital Adequacy Ratio, Loan to Deposit Ratio, Non Performing Loans and capitalization. The data in this study were obtained from the Indonesia Stock Exchange (BEI) from 2013 to 2017. The sampling technique used was purposive sampling. The sample used was 160 data from conventional commercial banks in Indonesia. Input variables for calculations using the DEA method are Third Party Funds and Total Assets. While the output variables used are credit distribution and operating income. The results showed that bank size and capitalization did not affect the level of banking efficiency. Meanwhile, Capital Adequacy Ratio and Non-Performing Loans negatifly affect the level of banking efficiency, while the Loan to Deposit Ratio has a positive effect on the level of banking efficiency.